Effect of Multiwalled Carbon Nanotubes and Electroless Copper Plating on the Tensile Behavior of Carbon Fiber Reinforced Polymers - Gia Toai Truong; Jiho Kim; Kyoung-Kyu Choi (Advances in Materials Science and Engineering)
Multiwalled carbon nanotubes (MWCNTs) and nanoscaled electroless copper plating were introduced to enhance the mechanical properties of carbon fiber reinforced polymer (CFRP) composites in this study. The influence of multiwalled carbon nanotubes (MWCNTs) with weight fractions of 0.5–1.5% of epoxy resin on the mechanical properties of CFRP composites was investigated. The MWCNTs and epoxy resin was first mixed, prior to impregnating the carbon fiber fabrics. Electroless copper plating, a deposit method using simultaneous reactions in an aqueous (copper) solution without external electric power, was applied on the carbon fiber surface, and the effect was also investigated. The CFRP test specimens were fabricated by hand lay-up method, using one or three carbon fiber fabrics. The mechanical properties of the CFRP test specimens were derived by tensile tests according to KS M ISO 527-4. According to the morphology taken by SEM, the carbon fiber surface was significantly rough with copper ions. Because of this, the strength and ultimate strain of coated specimens increased up to 26.3 and 18.6% compared to noncoated specimens, respectively. In addition, as the MWCNTs amount increased, the ultimate strain of the composites also increased. In the case of CFRP test specimens using noncoated carbon fiber fabrics, the addition of 1.5% wt. MWCNTs increased the peak strength and ultimate strain of CFRP specimens up to 80.5 and 48.8%, respectively. Finally, the tensile stress-strain relationship of CFRP specimens was idealized as bilinear or trilinear response curves.